First report on the characterization of pathogenic Rahnella aquatilis KCL‐5 from crucian carp: Revealed by genomic and proteomic analyses. Issue 8 (30th June 2020) - Liang, Jing; Hu, Xiucai; Lü, Aijun; Sun, Jingfeng
Abstract: Rahnella aquatilis is an important pathogen of several aquatic organisms and is found widely distributed in the freshwater, soil, fish and human clinical samples. Our previously published study reported a novel pathogenic R. aquatilis strain KCL‐5 to crucian carp ( Carassius auratus ). To further investigate the characteristics and pathogenesis caused by R. aquatilis, we here report on the pathological changes, bacterial genomic and proteomic analyses of strain KCL‐5. Significantly pathological changes in liver, intestine, spleen and gills were observed in infected fish. The genome consists of one circular chromosome 5, 062, 299 bp with 52.02% GC content and two plasmids (506, 827 bp, 52.16%; 173, 433 bp, 50.00%) and predicted 5, 653 genes, 77 tRNAs and 22 rRNAs. Some virulence factors were characterized, including outer membrane protein, haemolysin, RTX toxin, chemotaxis and T3SS secretion system. Antimicrobial resistance genes such as EmrAB‐TolC, MexABC‐OpmB and RosAB efflux pump were found in strain KCL‐5. KEGG analysis showed that mainly functional modules were ABC transporters, biosynthesis of amino acids, two‐component system, quorum sensing, flagellum assembly and chemotaxis, in which most of them were identified by using 2‐DE/MS analyses. To our knowledge, this was first report on the molecular characteristics of R. aquatilis by multi‐omics approaches, which will provide insights into the pathogenic mechanism of R. aquatilis infection in fish.